193k views
0 votes
HELP ASAP

The points $(-3,2)$ and $(-2,3)$ lie on a circle whose center is on the $x$-axis. What is the radius of the circle?

User EngBIRD
by
5.1k points

1 Answer

3 votes

Answer:


radius = √(13) or
radius = 3.61

Explanation:

Given

Points:

A(-3,2) and B(-2,3)

Required

Determine the radius of the circle

First, we have to determine the center of the circle;

Since the circle has its center on the x axis; the coordinates of the center is;


Center = (x,0)

Next is to determine the value of x through the formula of radius;


radius = √((x_1 - x)^2 + (y_1 - y)^2) = √((x_2 - x)^2 + (y_2 - y)^2)

Considering the given points


A(x_1,y_1) = A(-3,2)


B(x_2,y_2) = B(-2,3)


Center(x,y) =Center (x,0)

Substitute values for
x,y,x_1,y_1,x_2,y_2 in the above formula

We have:


√((-3 - x)^2 + (2 - 0)^2) = √((-2 - x)^2 + (3 - 0)^2)

Evaluate the brackets


√((-(3 + x))^2 + 2^2) = √((-(2 + x))^2 + 3 ^2)


√((-(3 + x))^2 + 4) = √((-(2 + x))^2 + 9)

Eva;uate all squares


√((-(3 + x))(-(3 + x)) + 4) = √((-(2 + x))(-(2 + x)) + 9)


√((3 + x)(3 + x) + 4) = √((2 + x)(2 + x) + 9)

Take square of both sides


(3 + x)(3 + x) + 4 = (2 + x)(2 + x) + 9

Evaluate the brackets


3(3 + x) +x(3 + x) + 4 = 2(2 + x) +x(2 + x) + 9


9 + 3x +3x + x^2 + 4 = 4 + 2x +2x + x^2 + 9


9 + 6x + x^2 + 4 = 4 + 4x + x^2 + 9

Collect Like Terms


6x -4x + x^2 -x^2 = 4 -4 + 9 - 9


2x = 0

Divide both sides by 2


x = 0

This implies the the center of the circle is


Center = (x,0)

Substitute 0 for x


Center = (0,0)

Substitute 0 for x and y in any of the radius formula


radius = √((x_1 - 0)^2 + (y_1 - 0)^2)


radius = √((x_1)^2 + (y_1)^2)

Considering that we used x1 and y1;

In this case we have that;
A(x_1,y_1) = A(-3,2)

Substitute -3 for x1 and 2 for y1


radius = √((-3)^2 + (2)^2)


radius = √(13)


radius = 3.61 ---Approximated

User Avtar Singh
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.